ANALISIS LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Wahyuni, Asri Nur; K.H., Suryakusuma (Jurnal Manajemen, 2018)
The purpose of this research to determine the effect of liquidity, solvency and corporate activity on corporate profitability on go public company of manufacturing sector in 2012-2016. Sampling is done by purposive sampling method. The use of multiple linear regression test with all classical assumption tests such as multicollinearity, autocorrelation, heteroscedasticity and normality tests showed that the regression model is feasible to use and pass all classical assumption tests. Partial significance test (t test) shows the results of liquidity, solvency and corporate activity have partially significant effect on corporate profitability and simultaneous significance test results (F test) show that all independent variables significantly influence the profitability of the company.